Policing Cyberspace: Understanding Online Repression in Thailand and the Philippines - Fernan Talamayan (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2020)
Social networking sites have become increasingly relevant in the study of democracy and culture in recent years. This study explores the interconnectedness of social networks, the imposition of state control, and management of social behavior by comparing various literature on the operation of repression in Thai and Philippine cyberspaces. It examines the overt and covert policing of daily interactions in digital environments and unpacks governmental technologies’ disciplinary mechanisms following Michel Foucault’s notion of government and biopolitical power. Subjugation in the context of social networks merits analysis for it sheds light on the practice of active and passive self-censorship—the former driven by the pursuit of a moral self-image and the latter by state-sponsored fear. In tracing various points of convergence and divergence in the practice of cyber control in Thailand and the Philippines, the study found newer domains of regulation of social behavior applicable to today’s democracies.